Analysis Model of Giant Prawns Population (Macrobrachium rosenbergii) in Estuary Edge of Sembakung Waters, Nunukan, Indonesia - Agus Indarjo; Gazali Salim; Christine Dyta Nugraeni; Lukman Yudho Prakoso; Permana Ari Soejarwo; Rukisah Rukisah; Yen Thi Hong Pham; Achmad Daengs GS; Hariyadi Hariyadi; Abdul Jabarsyah (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightThe sex ratio of giant prawns in the waters of fe- male groceries is 3 times higher than that of males.The growth characteristic of male and female   giant   prawns   is   negative   allometry, but the male and female body shapes are fat.Total   mortality, capture mortality, catch rate, male prawns are higher than females.The male infinitive growth is longer than the female,but the female's growth rate is faster than male.AbstractGiant prawns (Macrobrachium rosenbergii) is a crustacean class that has the larg- est size and its habitat in Sembakung waters included brackish water (estuarine) with a salinity variable of 6.5+0.5 ppt and a temperature variable of 28.5+0.5OC and a variable pH of 6 (acidic). The objective of this research was to analyze the growth and mortality model of giant prawns (M. rosenbergii) that was taken from the catch of fisherman in the estuary, Sembakung sub-district, Nunukan Regency, Indonesia. The study was conducted for 3 months from November 2019 to Janu- ary 2020. The sampling was by using a survey method with purposive judgment sampling based on a catch of 14 fishermen who used the bottom fish pot from Sembakung waters, Nunukan Regency (Indonesia). The data collection included data of sex, total length, and the total weight of giant prawns. While analysis was employed for growth pattern, condition index, Von Bertalanffy growth, and mor- tality. The results obtain the sex ratio of male and female giant prawns 1:3.67. The growth pattern of male and female giant prawns were allometric negative. The growth of the von Bertalanffy model for infinitive growth of male giant prawns were 21.219 cm and female were 18.42 cm, respectively the mortality from giant prawns obtain total male mortality is 2,257, catch mortality is 1.92 and natural mortality is 33.75% with an exploitation rate of 0.85 (85%). The total female mor- tality is 1.528, catch mortality is 120.1% and natural mortality is 32.69% with an exploitation rate of 0.786 (78.6%).